Factors influencing the purchase intention of Korean beauty products among Malaysian females - Tan, Day Shin; Thanasegaran, Ganesh; Manickiam, Neelamehan; Sidek, Shafie; Ismail, Kamarulzaman; Jantan, Amer Hamzah (Science and Engineering Research Support Society, 2020)
The Korean Wave or Hallyu is perceived as mainstream culture today in the 21st century, and it is well-accepted particularly in Asia. Korean entertainment which includes K-pop music, Korean drama series and variety programs have contributed to the immense popularity of the Korean Wave. This has resulted in an increasing interest in and demand for Korean products, including Korean beauty products. Since the K-Wave has also been fairly widely embraced by Malaysians especially females, this study attempts to investigate the relationship between K-Wave, the marketing mix variables (4Ps), and the purchase intention of Korean beauty products among Malaysian females. The independent variables selected for this study were K-Wave, product attributes (specifically product quality and brand), price, promotion and place (distribution), while the dependent variable was purchase intention of Korean beauty products among Malaysian females. Multiple linear regression analysis was performed to test the relationships and the findings confirmed that K-Wave, product quality, price and promotion were significant, implying that these factors did influence the purchase intention of Korean beauty products. However, brand and place (distribution) were found to be insignificant suggesting that there was no relationship between these two variables and the adoption of Korean beauty products among Malaysian females.